Francisco de Vitoria: the legitimate Indian titles - Burillo Loshuertos, Jesús (GLOSSAE. European Journal of Legal History, 1988)
Francisco de Vitoria, teacher and educator of a new generation of theologians, jurists, politicians and missionaries, had a decisive influence on the destiny of Spain. Vitoria directly posed the fundamental question of the corresponding juridical titles of the conquest and solved them according to the rules of the strictest scholastic method.